Platelet-Sourced TGF-β Promotes Th17 Responses and Enhances Airway Neutrophilia - Ruoning Wang; Dandan Wu; Chunqing Wang; Amanda Livingston; Xiang Wu; Meilian Liu; Xuexian O. Yang (Biomolecules)
Microbial, especially fungal, sensitization has been associated with the development and exacerbation of treatment-refractory neutrophilic asthma. Among the airway-inhabiting fungi, Aspergillus fumigatus and Candida albicans are the dominant species that elicit protective T helper (Th) 17 and other T cell responses, contributing to airway neutrophilia and steroid resistance. However, it is not fully understood how fungal airway colonization impacts the immunopathogenesis of asthma. Here, we used a neutrophilic asthma model induced by C. albicans to study the immune regulation of this disease. We found that intranasal administration of C. albicans induced platelet infiltration into the lung. Platelet-expressed latent TGF-β could be activated specifically by Th17 cells and drive the commitment, maintenance, and expansion of Th17 cells. In Candida-induced asthma, an adoptive transfer of platelets enhanced Th17 responses, increasing airway neutrophil influx. Thus, managing airway mycobiota and reducing platelet intrapulmonary infiltration may serve as a promising interventional approach.